Research on Trypanosoma cruzi and Analysis of Inflammatory Infiltrate in Esophagus and Colon from Chronic Chagasic Patients with and without Mega - Eliângela de Castro Côbo; Thales Parenti Silveira; Adilha Misson Micheletti; Eduardo Crema; Sheila Jorge Adad (Journal of Tropical Medicine)
To compare parasitism and inflammatory process in esophagus and colon from chronic chagasic patients, immunohistochemistry was carried out to research for T. cruzi and to evaluate the inflammatory infiltrate in the muscular and myenteric plexus in 39 esophagi (20 with and 19 without megaesophagus) and 50 colons (25 with and 25 without megacolon). The frequency of T. cruzi in megaesophagus was 20%, and in megacolon it was 4%. No amastigotes were found in organs without mega; considering the total of esophagi (with and without mega), the frequency of T. cruzi would be 10% and 2% in the colon. Myositis and ganglionitis were more frequent and intense in organs with mega compared to those without mega, and in esophagus compared to colon. Qualitatively, inflammatory infiltration in esophagus and colon, with or without mega, was similar, consisting predominantly of T lymphocytes (CD3+), scarce macrophages (CD68+), and rare B lymphocytes (CD20+).